Case Report: A rare case of renal failure secondary to in utero megalourethra - Ali, S.; Nunez, V.; Terkawi, R.; Katsoufis, C.; Abitbol, C.; Ruano, R.; Duara, J.; Fontanez-Nieves, T. (Frontiers in Pediatrics, 2025)
BackgroundMegalourethra is a rare congenital condition marked by dilation and elongation of the penile urethra, resulting from hypoplasia of either the corpus spongiosum or corpus cavernosa.Case presentationWe describe a novel case of a male infant prenatally diagnosed with megalourethra who subsequently developed rapid-onset anhydramnios and advanced renal failure.ConclusionUnlike previously described cases, this case is unique due to the patient's abrupt progression to anhydramnios at 34 weeks and 5 days, despite having normal amniotic fluid levels prior to that. With late-onset anhydramnios, the severity of renal dysfunction was unexpected. Proximal urethrostomy requires further assessment as a potential intervention to successfully bypass the megalourethra and prevent infection. Long-term management is expected to include dialysis as a bridge to transplantation. Multiple corrective urological surgeries will be required to repair the urethra and restore penile function. Timely prenatal diagnosis of megalourethra or renal anomalies is essential for predicting long-term prognosis, as these conditions can lead to significant postnatal complications.